Accelerating photosensitized H2 evolution over in situ grown amorphous MoSx catalyst employing TiO2 as an efficient catalyst loading matrix and electron transfer relay. (August 2019) - Liu, Xiangyu; Min, Shixiong; Xue, Yuan; Lei, Yonggang; Chen, Yangyang; Wang, Fang; Zhang, Zhengguo
Abstract: Although dye sensitized photocatalytic systems employing in situ grown amorphous MoSx as catalyst have shown promising performance for H2 evolution reaction (HER), their low activity and short durability need to be further improved. Herein, we report that employing TiO2 as an electron relay and catalyst loading matrix can greatly accelerate the H2 evolution activity of in situ grown MoSx in an Eosin Y (EY) sensitized system. The EY/TiO2 /MoSx system exhibited 4.5 times higher H2 evolution activity than EY/MoSx and an apparent quantum yield (AQY) of 27.5% at 500 nm. The TiO2 /MoSx catalyst also showed improved stability as compared to free MoSx . The enhanced H2 evolution activity of EY/TiO2 /MoSx system was attributed to the presence of TiO2, which can not only serve as an effective loading matrix to grow MoSx with high dispersion and reduced size, affording an abundance of active sites toward HER, but also efficiently mediate the electron transfer from excited EY (EY ∗ ) to MoSx, leading to the promoted oxidative quenching of EY ∗, and thus suppressing the formation of unstable EY −· . This work provides an effective strategy to develop highly active noble-metal-free H2 evolution systems by simultaneously regulating electron transfer kinetics and existing state of catalyst with multifunctional mediators. Graphical abstract: Image 1 Highlights: Amorphous MoSx was loaded on TiO2 with the in situ photosensitization method. MoSx grown on TiO2 has smaller size and higher dispersion than free MoSx . The presence of TiO2 can facilitate the electron transfer from excited EY to MoSx . TiO2 /MoSx catalyst exhibits 4.5 times higher activity and stability than free MoSx catalyst. The highest apparent quantum yield of 27.5% is obtained in EY/TiO2 /MoSx system at 500 nm.